Finding phase information in the darkness - Haigh, S; Kirkland, A (2010)
High resolution local structure information is revealed when the complex exit wavefunction is restored from a series of transmission electron microscope (TEM) images. Aberration corrected image data sets allow high spatial frequency information to be restored but this is often at the expense of lower spatial frequencies. In this paper we present a new approach to exit wavefunction restoration using a novel five image focal series with non-uniform focal steps. This data set extends the spatial frequency range over which information can be successfully restored. We present simulation studies comparing this approach to a conventional focal series and demonstrate the benefit of including low spatial frequencies in the restoration. We propose that this approach will be important for the study of large unit cell materials or those with long range ordering. © 2010 IOP Publishing Ltd.